2000
DOI: 10.2460/ajvr.2000.61.330
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the safety of fenbendazole in cats

Abstract: Fenbendazole administered to healthy cats at a dosage 5 times the dosage and 3 times the duration approved for use in dogs and wild felids did not cause any acute or subacute adverse reactions or pathologic changes. Results suggest that cats may be safely treated with fenbendazole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 6 publications
0
10
0
2
Order By: Relevance
“…When given therapeutically to nonpregnant animals, benzimidazoles produce few adverse effects, even when given in doses several times in excess of those recommended. Thus, fenbendazole produced no adverse effects in cats when given at up to five times the recommended dose and three times the recommended duration (Schwartz et al, 2000). No toxic effects were seen in cattle given 2000 mg/kg body weight fenbendazole (the therapeutic dose is around 5 mg/kg body weight) (Muser & Paul, 1984).…”
Section: Benzimidazole Anthelmintic Drugsmentioning
confidence: 99%
“…When given therapeutically to nonpregnant animals, benzimidazoles produce few adverse effects, even when given in doses several times in excess of those recommended. Thus, fenbendazole produced no adverse effects in cats when given at up to five times the recommended dose and three times the recommended duration (Schwartz et al, 2000). No toxic effects were seen in cattle given 2000 mg/kg body weight fenbendazole (the therapeutic dose is around 5 mg/kg body weight) (Muser & Paul, 1984).…”
Section: Benzimidazole Anthelmintic Drugsmentioning
confidence: 99%
“…11,12 FEN has demonstrated very low toxicity in various animal species including dogs. [13][14][15][16] Moreover, several studies conducted on cancer cell treatment reported positive effects of FEN. Chu et al demonstrated that benzimidazoles such as FEN and albendazole destroyed microtubules, induced apoptosis, and inhibited drug resistance in human ovarian cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Fenbendazole (methyl N-(6-phenylsulfanyl-1Hbenzimidazol-2-yl) carbamate) is a broadspectrum benzimidazole anthelmintic that contains anti-proliferative activity and is typically used in veterinary medicine to target parasitic pinworms. Fenbendazole is also known to have low degree of toxicity and high degree of safety in animals [26][27][28][29][30]. Fenbendazole is used to target gastrointestinal parasites including: giardia, roundworms, hookworms, whipworms, the tapeworm genus Taenia -excluding dipylidium caninum, which is a common dog tapeworm -, pinworms, aelurostrongylus, paragonimiasis, strongyles, and strongyloides.…”
Section: Fenbendazolementioning
confidence: 99%